Analisis Karakteristik Modul PV Monocrystalline dan Polycrystalline di Lingkungan Tropis - Muhammad Basyir; Aidi Finawan; Arsy Febrina Dewi; Yuli Mauliza; M Fitri Anggito Sitorus (VOCATECH: Vocational Education and Technology Journal, 2026)
Monocrystalline and polycrystalline photovoltaic modules continue to dominate solar power system applications; however, experimental evidence based on field measurements in tropical environments remains relatively limited. This study aims to analyze and compare the performance of both PV module types through outdoor testing conducted over 30 days in Indonesia, considering the combined effects of module temperature, dust deposition, and relative humidity. The method employed was comparative field testing with real-time monitoring of key electrical parameters, namely voltage, current, and power, as well as environmental variables. The results indicate that monocrystalline modules consistently outperform polycrystalline modules, with an average power output of 102.4 W (8.6% higher) and a conversion efficiency of 17.8% (11.9% higher). Statistical analysis confirms that the performance difference is significant (p 0.0001; Cohen’s d = 1.85). Module operating temperature was identified as the dominant factor contributing to power degradation, followed by dust and humidity. Collectively, these three environmental factors resulted in an estimated power loss of 13.4% for monocrystalline modules and 16.0% for polycrystalline modules. These findings suggest that monocrystalline modules are better suited for small-scale and residential PV applications in tropical regions due to their superior performance, higher efficiency, and greater thermal resilience.